Folding of disulfide proteins - Chang, Rowen J. Y.; Ventura, Salvador (Protein reviews, 2011)
Disulfide-containing proteins belong to a unique class of proteins for studying the mechanism of protein folding. Their folding mechanism can be analyzed by three distinct techniques: (1) The conventional denaturation-renaturation method (disulfide intact); (2) The disulfide oxidation method (oxidative folding); and (3) The emerging disulfide scrambling method. Each technique provides specific information as to how an unfolded disulfide protein refolds to form the native structure. This book is intended to highlight the knowledge of several important proteins (BPTI, RNase A, beta-Lactalbumin and Lysozyme etc.) that have been characterized in depth by these methodologies. The book will also devote sections to comparing these methodologies and chaperones (PDI and Dsb machineries) that facilitate folding of disulfide proteins. Folding of Disulfide Proteins aims to cover the knowledge of protein folding accumulated from studies of disulfide-containing proteins, including methodologies, folding pathways, and folding mechanism of numerous extensively characterized disulfide proteins. This book will be of interest to those interested in problems related to protein folding, and anyone who is interested in understanding the mechanism of protein misfolding and protein misfolding-related diseases. Folding of Disulfide Proteins aims to cover the knowledge of protein folding accumulated from studies of disulfide-containing proteins, including methodologies, folding pathways, and folding mechanism of numerous extensively characterized disulfide proteins. This book will be of interest to those interested in problems related to protein folding, and anyone who is interested in understanding the mechanism of protein misfolding and protein misfolding-related diseases.